Loss of Type A neuronal cells in the dorsal root ganglion after a non-severe full-thickness burn injury in a rodent model. Issue 7 (November 2018) - Palanivelu, Vetrichevvel; Maghami, Siaavash; Wallace, Hilary J.; Wijeratne, Dulharie; Wood, Fiona M.; Fear, Mark W.
Abstract: Burn scars can be associated with significant loss of cutaneous sensation, paresthesia and chronic pain. Long-term systemic changes in cutaneous innervation may contribute to these symptoms and dorsal root ganglia have been implicated in the development of chronic neuropathic pain. Therefore we hypothesized that changes in cutaneous innervation after burn injury may be mediated at the level of the dorsal root ganglia. Burn group rats (n = 20) were subjected to a unilateral burn injury while 12 control rats underwent sham procedure. The DRGs dermatomally related to the site of burn (Thoracic 13, lumbar 1 and lumbar 2), ipsilateral and contralateral to the injury, were compared for Type A, Type B and total cell number with sham control DRGs, at 4 and 6 weeks after injury. There was a significant decrease in Type A cell count (cell bodies of nerve fibres mediating touch-pressure-vibration sensation) in the 4 week time-point group (p = 0.0124) ipsilateral to the burn injury. Total DRG cell count and Type B DRG cell count (cell bodies of fibres mediating pain and itch) on the ipsilateral side was not significantly altered. On the side contralateral to the burn injury, there was no statistically significant change in the total cell count, Type A cell count or Type B cell count. This data showed a decrease in Type A cell number in DRGs after a burn injury, suggesting cell death may mediate some changes observed in cutaneous innervation after a burn. Type B cells constituted a greater proportion of the viable cell population in the ipsilateral DRG after a burn injury. This change may be important in the induction of signalling related to pain and itch and has important implications for the restoration of normal cutaneous innervation after burn injury. Investigating whether neuro-protective or neuro-restorative approaches can ameliorate damage to the DRG will be important to improve sensory outcomes for burn patients.